The impact of information acquisition ability on consumers' trust in eco-labels in China: insight of food sustainability - Yang, Yanyan; Xue, Fang; Qiao, Guanghua (Frontiers in Sustainable Food Systems, 2024)
The lack of trust in eco-labels is a significant reason for the slow growth in demand for sustainable food, and reducing the information gap between relevant parties is a crucial means to improve consumer trust in eco-labels. In order to investigate the influence and driving pathways of consumers' information acquisition abilities on their trust in eco-labels, a total of 1,072 urban and rural consumers in Inner Mongolia, China were surveyed in this study, with an analysis conducted using the structural equation model. It was found that information acquisition ability, institutional trust, and label knowledge have significant direct impacts on eco-label trust, with impact effects of 0.270, 0.351, and 0.357, respectively. Additionally, information acquisition ability has indirect effect of 0.085 and 0.127 on label trust through institutional trust and label knowledge. Furthermore, information discernment awareness has a significant negative moderating effect between information acquisition ability and label trust. Therefore, when publicizing the certification system and label knowledge, cultivating consumers' information acquisition ability effectively enhances eco-label trust.Moreover, strengthening media supervision to ensure the authenticity and objectivity of information transmission is an important measure to protect trust in eco-labels. This study enriches relevant research in the field of food sustainability and provides valuable recommendations to promote sustainable food consumption.